Novel Mechanisms for IGF-I Regulation by Glucagon in Carp Hepatocytes: Up-Regulation of HNF1α and CREB Expression via Signaling Crosstalk for IGF-I Gene Transcription - Bai, Jin; Jiang, Xue; He, Mulan; Chan, Ben C. B.; Wong, Anderson O. L. (Frontiers in Endocrinology, 2019)
Glucagon, a key hormone for glucose homeostasis, can exert functional crosstalk with somatotropic axis via modification of IGF-I expression. However, its effect on IGF-I regulation is highly variable in different studies and the mechanisms involved are largely unknown. Using grass carp as a model, the signal transduction and transcriptional mechanisms for IGF-I regulation by glucagon were examined in Cyprinid species. As a first step, the carp HNF1α, a liver-enriched transcription factor, was cloned and confirmed to be a single-copy gene expressed in the liver. In grass carp hepatocytes, glucagon treatment could elevate IGF-I, HNF1α and CREB mRNA levels, induce CREB phosphorylation, and up-regulate HNF1α and CREB protein expression. The effects on IGF-I, HNF1α and CREB gene expression were mediated by cAMP/PKA and PLC/IP3/PKC pathways with differential coupling with the MAPK and PI3K/Akt cascades. During the process, protein:protein interaction between HNF1α and CREB and recruitment of RNA Pol-II to IGF-I promoter also occurred with a rise in IGF-I primary transcript level. In parallel study to examine grass carp IGF-I promoter activity expressed in αT3 cells, similar pathways for post-receptor signaling were also confirmed in glucagon-induced IGF-I promoter activation and the trans-activating effect by glucagon was mediated by the binding sites for HNF1α and CREB located in the proximal region of IGF-I promoter. Our findings, as a whole, shed light on a previously undescribed mechanism for glucagon-induced IGF-I gene expression by increasing HNF1α and CREB production via functional crosstalk of post-receptor signaling. Probably, by protein:protein interaction between the two transcription factors and subsequent transactivation via their respective cis-acting elements in the IGF-I promoter, IGF-I gene transcription can be initiated by glucagon at the hepatic level.